Education, Health and Technology in Indonesia's Economic Recovery Efforts Based on Three Human Performance Theory - Sebastiana Viphindrartin; suryaning Bawono (LPPM of NAROTAMA UNIVERSITY, 2021)
This study aims to examine the gap between human capital theory and allocation theory in Indonesia to see the dominant factors driving economic growth by making the solow theory a bridge theory or an intermediary between the gap between human capital theory and allocation theory. In order to understand and test the human capital theory and allocation theory in Indonesia, testing is carried out using the autoregressive threshold quantitative method. The use of the autoregressive Threshold quantitative method aims to see the behaviour of data from the education, health and technology variables so that it can be seen clearly that the dominance of the economic growth drive comes from human capital or from the human side in accordance with the explanation of human theory or from the outside of the human self and in this study technology as explained by the allocation theory. We find that in Indonesia, the role of human capital is very important because human capital in the case of Indonesia is a major factor in driving economic growth and technology plays a role as a supporter of human performance. This is in accordance with the human capital theory and does not support the allocation theory